Strategies for Sustainable Ecotourism Development in Sangeh Conservation Forest in Badung Bali - Said Fahmi; Mutia Herni Ningrum; Khaerul Amru; Aulia Nur Laksmita; Erwika Dhora Jati (School of Postgraduate Studies, Diponegoro Univer, 2023)
ABSTRACTThe sustainable development strategy is a strategy that is oriented towards the importance of environmental preservation. This study aims to examine more deeply the potential of the Sangeh Conservation Forest, both in terms of abiotic, biotic, and cultural aspects, so that a sustainable ecotourism development strategy can be formulated. The method that used in this research was collecting primary data through observation and interviews. The sample was determined based on purposive sampling then was processed qualitatively and descriptively with the SWOT analysis technique. The results of the analysis shows that there were various great ecotourism potentials from TWA Sangeh. TWA Sangeh has great potential to become a center of biodiversity conservation education and cultural tourism. There were weaknesses in the potential development of TWA Sangeh which can be overcome by efforts such as improving the quality of human resources for tourism managers through special training in tourism and monitoring of biodiversity at TWA Sangeh. All efforts regarding sustainable development can run through the role of tourism managers and stakeholders whom support resiprocally.